Social Representations of the Curriculum in Physical Education Teachers: A Multi-Method Analysis regarding Teachers from Copacabana, Colombia - Roger Alexander González Ramírez; Enoc Valentin González Palacio (Physical Education Theory and Methodology)
Objectives. This study aimed to provide a specific analysis of social representations on the curriculum in physical education teachers.